Comparison of the Profile and TSH Levels from Several Types of Blood Collection Tubes - Gunawan Eka Putra; Ninik Sukartini; Suzanna Immanuel; Fify Henrika; Nuri Dyah Indrasari (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2020)
Thyroid-Stimulating Hormone (TSH) is an important parameter in diagnosing thyroid disease which uses serum according to the World Health Organization's (WHO) recommendations. The use of plasma can help improve the Turn Around Time (TAT); however, the discrepancy with serum is unknown. A cross-sectional study using 89 blood samples was performed to compare TSH levels using serum tubes with clot activator (Tube I), plasma tubes with heparin (Tube II), and plasma tubes with heparin-gel separator (Tube III); and to overview of TSH levels according to gender and age. The median of TSH levels in Tubes I, II, and III were 1.380 (0.032-7.420) Î¼IU/mL, 1.380 (0.030-7.480) Î¼IU/mL, and 1.360 (0.030-7.460) Î¼IU/mL, respectively. There were no statistically significant differences in TSH levels of the three tubes. The median TSH levels differences of Tubes II and III compared to the tube I were -0.9% (-7.2-2.2) and -1.7% (-8.0-1.6), respectively. Measurement bias observed in this study was following the specified desirable bias according to Ricos. The median TSH levels of the male and female groups were 1.500 (0.032-4.250) Î¼IU/mL and 1.345 (0.058-7.420) Î¼IU/mL, respectively. Median TSH levels of 31-40 years old age group and >61 years old age group were 1.190 (0.609-3.240) Î¼IU/mL and 1.730 (0.088-5.760) Î¼IU/mL, respectively. Specimens from three tubes could be used to examine TSH levels. Measurement of TSH levels showed a higher median in the male and older group.